2021
DOI: 10.1101/2021.08.05.455126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical nanoscopy reveals SARS-CoV-2-induced remodeling of human airway cells

Abstract: A better understanding of host cell remodeling by the coronavirus SARS-CoV-2 is urgently needed to understand viral pathogenesis and guide drug development. Expression profiling and electron microscopy have frequently been used to study virus-host interactions, but these techniques do not readily enable spatial, sub-cellular and molecular analysis of specific cellular compartments. Here, we use diffraction-unlimited fluorescence microscopy to analyze how SARS-CoV-2 infection exploits and repurposes the subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 81 publications
1
8
1
Order By: Relevance
“…COVID-19 pandemic caused by SARS-CoV-2 poses a severe threat to global health due to the high transmissibility, broad cell tropism, and post-acute sequelae (Groff et al 2021, Ramos da Silva et al 2021, Lee et al 2022). Our findings in this study highlight the crucial function of filopodia in the process of cell-free-virus invasion (Fig 6), which complement the previously reported role of filopodia during virus egress and cell-cell-transmission (Bouhaddou et al 2020, Barreto-Vieira et al 2021, Nijenhuis et al 2021, Pepe et al 2022, Swain et al 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…COVID-19 pandemic caused by SARS-CoV-2 poses a severe threat to global health due to the high transmissibility, broad cell tropism, and post-acute sequelae (Groff et al 2021, Ramos da Silva et al 2021, Lee et al 2022). Our findings in this study highlight the crucial function of filopodia in the process of cell-free-virus invasion (Fig 6), which complement the previously reported role of filopodia during virus egress and cell-cell-transmission (Bouhaddou et al 2020, Barreto-Vieira et al 2021, Nijenhuis et al 2021, Pepe et al 2022, Swain et al 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Many proteins are involved in regulating filopodia formation, such as actin cross-linking protein fascin, parallel actin nucleating protein formin, and branched actin nucleating protein Arp2/3 (Mellor 2010, Aliyu et al 2021). Recent studies reveal that larger number of elongated filopodia, microvilli, actin bundles, and stress fibers induced by SARS-CoV-2 infection are important for virus egress and/or cell-to-cell spread (Bouhaddou et al 2020, Barreto-Vieira et al 2021, Nijenhuis et al 2021). However, the morphological dynamics and the biological roles of filopodia during the invasion of SARS-CoV-2 remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Successful application of TREx to filter-cultured Caco-2 cells further demonstrates the robustness of TREx, because we had repeatedly failed to cleanly recover epithelial cultures using standard ExM. The robustness of TREx has been further demonstrated by its adoption in other biological systems (Gros, Damstra, Kapitein, Akhmanova, & Berger, 2021) including in cultured neurons (Ɩzkan et al, 2021) and primary cultured human cells (Nijenhuis et al, 2021), and by its superior mechanical properties as measured by traditional materials characterization methods (R. Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Several in vitro and in vivo studies have demonstrated proclivity for SARS-CoV-2 virus to ciliated cells, evidenced by prominent ciliary abnormalities (7)(8)(9) and impaired mucociliary clearance (10,11) in these model systems. Perhaps consequently, hyper viscous mucus in bronchoalveolar lavage (BAL) fluid (12)(13)(14) and in the airways (15,16) of COVID-19 patients have been reported, suggesting the clinical importance of these events.…”
Section: Introductionmentioning
confidence: 99%